Carotene Reduction Level in The Processing of Pumpkin Instant Brownies - Silvia Oktavia Nur Yudiastuti; Agung Wahyono; Yani Subaktilah (Journal Research of Social Science, Economics, and Management, 2021)
Pumpkin is a local food of Jember which the amount of harvested area and productivity is increasing every year. Pumpkin is a source of beta carotene with a relatively lower price than other beta carotene sources. Diversification of pumpkin-based food products will produce nutritionally rich products with added value. Brownies are one of the bakery products that can be processed with 100% pumpkin flour as raw material, increasing the added value can be done by diversifying it into semi-finished products with pumpkin steamed brownie premix flour. What needs to be evaluated in the diversification process is the change in the levels of carotene as its functional component. The research method used was descriptive evaluating changes in carotene in 6 treatments of pumpkin steamed brownies premix flour formulations. Based on the results of the study, the most abundant carotene was found in the 100% pumpkin flour formulation treatment, namely 77.99 mg/100g in premix flour and 5.05 mg/100g in steamed brownies. The higher the pumpkin content, the lower the degree of reduction in total carotene will be.